2008
DOI: 10.1097/jsa.0b013e3181824e76
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment of Chronic Distal Biceps Tendon Ruptures

Abstract: Chronic biceps tendon ruptures typically involve tendon retraction, scarring, and even compromised tissue. Indirect repair, such as tenodesis to the brachialis, does not provide optimal functional recovery. Chronic biceps tendon ruptures can be reconstructed with autogenous grafts (semitendinosis, tensor fascia lata) or allografts (typically Achilles tendon). The complications associated with these grafts include harvest site morbidity and graft incorporation. Using a vascularized local soft tissue source coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Surgical debridement and reattachment is only warranted in patients who fail to respond to conservative management (24,30,34,35). The majority of patients with complete tears require immediate surgical reattachment of the biceps tendon to the bicipital tuberosity (36), as delayed reconstruction of the tendon can be more challenging and have a poorer functional outcome (24,30,(37)(38)(39).…”
Section: Anterior Tendon Pathologymentioning
confidence: 99%
“…Surgical debridement and reattachment is only warranted in patients who fail to respond to conservative management (24,30,34,35). The majority of patients with complete tears require immediate surgical reattachment of the biceps tendon to the bicipital tuberosity (36), as delayed reconstruction of the tendon can be more challenging and have a poorer functional outcome (24,30,(37)(38)(39).…”
Section: Anterior Tendon Pathologymentioning
confidence: 99%
“…16 However, current advancements in reconstructive surgical techniques have led to improved function and decreased complications resulting from surgical intervention. 2,5 Thus, operative fixation is currently recommended for most patients with chronic distal biceps tendon ruptures, except those who are low demand or not fit for surgery. 2 We have presented a series of chronic distal biceps tendon reconstructions using a fascia lata autograft, performed through a modified, anterior approach and secured to the biceps tubercle with suture anchors.…”
Section: Discussionmentioning
confidence: 99%
“…In general, reconstruction, rather than primary repair, is necessary after 6 weeks due to tendon retraction, scar formation and tissue atrophy. 5 Operative techniques described include tenodesis to the brachialis and anatomic reconstruction using tendon grafts. 6 Graft options include local lacertus fibrosis, 5 autograft semitendinosis, 7 split flexor carpi radialis, 8 palmaris longus 9 and fascia lata, 10 and Achilles tendon allograft.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have suggested using the lacertus fibrosus as a local graft source in chronic DBT tears. 16 …”
Section: Relevant Anatomymentioning
confidence: 99%